Response of atmospheric CO2 changes to the Abyssal Pacific overturning during the last glacial cycle - Zhang, Yanan; Li, Gang; Yu, Jimin; Yi ZHONG; Du, Jianghui; Gong, Xun; Jiang, Xiaodong; Gai, Congcong; Li, Shiying; Liu, Qingsong (Global and Planetary Change, 2025)
Despite its critical role in regulating the global climate and carbon cycle, the evolution of deep Pacific circulation has not been fully deciphered during the last glacial cycle. The effect of deep Pacific hydrographic change (e.g. oxygenation and circulation) on atmospheric CO2 variation is still uncertain. Here, we study redox-sensitive elements including V-U-Mn and benthic foraminiferal δ13C at the HYIV2015-B9 site in the southern South China Sea (SCS) to reconstruct the oxygenation and δ13C signals of water masses during the last glacial cycle. The intra-basin benthic foraminiferal δ13C gradient suggests enhanced stratification of the deep Pacific during the glacial compared to the interglacial, implying sluggish abyssal Pacific overturning. This is consistent with weak Pacific Deep Water (PDW) ventilation, as indicated by high contents of authigenic V and U, and low authigenic Mn. The inferred sluggish abyssal Pacific overturning is probably associated with less transport of Lower Circumpolar Deep Water, facilitating the expansion of respired carbon storage in the glacial deep Pacific. Meanwhile, the atmospheric CO2 rise is closely related to active abyssal Pacific overturning since late MIS 5, particularly when considering the impact of Southern Ocean upwelling modulated by Earth's obliquity. Overall, our data indicate the critical role of abyssal Pacific overturning in the carbon cycle, revealing the potential pathway for deep carbon dioxide outgassing in the North Pacific.
Keywords: Abyssal Pacific overturning; Benthic δC; Global carbon cycle; Last glacial cycle; Oxygenation history